Comparison of Efficacy of Vaginal and Intramuscular Progesterone in Preventing Preterm Birth in High-Risk Pregnant Women - Hina; Zaib Un Nisa; Zeenat Un Nisa; Shams Un Nisa; Khan, Roona (Indus Journal of Bioscience Research, 2024)
Objective: To compare the efficacy of vaginal and intramuscular progesterone in preventing preterm birth among high-risk pregnant women. Material and Methods: This cross-sectional study included 100 high-risk pregnant women at gestational ages <37 weeks. Participants were randomly assigned to receive either 200 mg daily vaginal progesterone suppositories (Group A) or 250 mg weekly intramuscular 17α-hydroxyprogesterone injections (Group B). Outcomes measured included gestational age at delivery, NICU admissions, APGAR scores, birth weight, and adverse effects. Data were analyzed using SPSS version 25, with statistical significance set at p≤0.05. Results: Group A showed 84% deliveries >37 weeks, compared to 86% in Group B (p>0.05). Normal deliveries were observed in 80% of Group A and 84% of Group B. NICU admissions occurred in 16% of Group A and 12% of Group B. Abnormal APGAR scores were reported in 14% of Group A and 4% of Group B. Both groups demonstrated comparable safety and efficacy. Conclusion: Vaginal and intramuscular progesterone exhibited similar efficacy in preventing preterm birth. Vaginal progesterone showed marginal advantages in neonatal outcomes and fewer systemic side effects.